PENGETAHUAN DAN PERAN IBU DALAM PENGENALAN SISTEM REPRODUKSI SEJAK DINI PADA ANAK USIA PRASEKOLAH (3-5 TAHUN) DI WILAYAH KERJA PUSKESMAS BERINGIN RAYA KOTA BENGKULU - Herawati, Neti (UNIVED Press, Universitas Dehasen Bengkulu, 2018)
Rampant cases of child sexual abuse in Indonesia to be the most worrying at this time, this was due to the lack of parents inintroducing reproductive system to children early because it was considered as taboo, parents only introduces the name of non genital parts of the body. In the city of Bengkulu sexual abuse of children each year increase. This study aimed to know the relationship between knowledge and the role of mothers in the introduction of the reproductive system early at the age of preschool children (3-5 years) in Beringin Raya Health Center.This study used a descriptive analytic method with cross sectional rangcangan. The population of this study were mothers of preschool children (3-5 years) in Beringi Raya Health Center Bengkulu City. The sampling technique used was proportional random sampling with data analysis using univariate and bivariate.Univariate analysis research results obtained over the majority of respondents (56.0%) had less knowledge about the reproductive system, the majority of respondents (72.0%) had less good role, and the majority of respondents (70.30%) were less in giving recognition to their reproductive system and test results statictik chi-square value of Ï value of knowledge gained 0,047 and the role Ï values obtained value of 0.021. Expected to teachers in kindergartens to provide education about reproduction on children and mothers of students to introduce the reproductive organs.